Conditions for Inception of Relativistic Runaway Discharges in Air. Issue 7 (30th March 2023) - Pasko, Victor P.; Celestin, Sebastien; Bourdon, Anne; Janalizadeh, Reza; Jansky, Jaroslav
Abstract: Terrestrial gamma‐ray flashes are linked to growth of long bidirectional lightning leader system consisting of positive and stepping negative leaders. The spatial extent of streamer zones of a typical lightning leader with tip potential exceeding several tens of megavolts is on the order of 10–100 m. The photoelectric absorption of bremsstrahlung radiation generated by avalanching relativistic runaway electrons occurs efficiently on the same spatial scales. The intense multiplication of these electrons is triggered when the size of the negative leader streamer zone crosses a threshold of approximately 100 m (for sea‐level air pressure conditions) allowing self‐replication of these avalanches due to the upstream relativistic electron seeds generated by the photoelectric absorption. The model results also highlight importance of electrode effects in interpretation of X‐ray emissions from centimeter to meter long laboratory discharges, in particular, a similar feedback effect produced by generation of runaway electrons from the cathode material. Plain Language Summary: We propose a physical mechanism that explains spectacular naturally occurring bursts of X‐rays that are observed in association with lightning activity in the Earth's atmosphere. These events are commonly referred to as terrestrial gamma ray flashes (TGFs). The mechanism is based on a feedback process allowing amplification of relativistic electron avalanches when X‐rays emitted by these electrons travel backwards with respect to the electron motion and generate new relativistic electron seeds due to the photoelectric absorption in air. The presented model results agree with the observational and experimental evidence indicating that TGFs are associated with steps of negative lightning leaders and originate from relatively compact regions of space with spatial extent on the order of 10–100 m. The mechanism is not sensitive to the origin and amount of the initial runaway electrons and identical results are obtained whether the initial seeds are provided by the natural background as cosmic ray secondaries or generated by the streamer discharges. We also provide quantitative evidence that in the presence of electrodes the same amplification mechanism and X‐ray production may involve generation of runaway electrons from the cathode material. These effects may be relevant to development of new X‐ray sources. Key Points: The onset of terrestrial gamma ray flashes is linked to the spatial extent of the lightning leader streamer zone The photoelectric absorption is the dominant feedback factor defining inception of relativistic runaway discharges in air The photoelectric absorption generated runaway electrons from the cathode facilitate X‐rays from laboratory sparks